Comparative studies on antisickling properties of brown and green leaves of Carica papaya Linn. (Caricaceae) - Glory Oluremilekun Ajayi; Ogun Olupelumi Maria (International Journal of Phytomedicine, 2017)
Sickle Cell Disease (SCD) is characterised by non-covalent polymerisation of the haemoglobin under hypoxia conditions and this promotes red blood cell sickling. Inhibition of sickle cell haemoglobin polymerization is one of the areas of focus in the management of SCD. Dried Carica papaya leaves are used in traditional herbal remedies for the management of sickle cell anaemia; without specifying if it is the dried green or brown leaf. This study was aimed at verifying the antisickling activity of the crude aqueous extract, crude methanol extract and fractions of dried brown and green leaves of Carica papaya. The method used was the sickle cell haemoglobin polymerization inhibition experiment measured with the Ultra Violet (UV) spectrophotometer. Sodium metabisulphite was used as a deoxygenating agent while isotonic saline (0.9% NaCl) was used as the negative control and phenylalanine as a positive control. The results obtained showed that crude aqueous extracts of both the green and brown leaves exhibited high level of inhibition of sickled haemoglobin (HbSS) polymerization at 200 mg/ml (97.76% and 93.25% ), 100 mg/ml (95.89% and 97.93%) also, 50 mg/ml (97.89% and 95.84%) respectively which compared favourably and significantly (p<0.05) with that of phenylalanine. The summary of the antisickling activity of the crude extracts and fractions of both the green leaves and brown leaves of C. papaya is Crude aqueous>Crude aqueous methanol> Butanol>Chloroform>Ethyl acetate>Aqueous. This study showed that the extracts exhibited the potential of inhibiting polymerization of sickle cell haemoglobin thus would be beneficial in the management of sickle cell disease.